Electronic health record implementation: how to identify and analyze the possible negative impacts - Paula Fuscaldo Calderon; Silvia Sato; Nelson Wolosker (Einstein (São Paulo), 2024)
ABSTRACT Objective Identify potential negative impacts arising from implementing an electronic medical record system, classify them according to the level of criticality, and analyze method’s effectiveness after implementation. Methods The research involved identifying the negative impacts, classifying them according to the criteria for criticality, stratifying them as high, medium, or low severity, and finally, analyzing the effectiveness of the identification and classification methods. Results Findings confirmed that 89.20% of identified impacts occurred as predicted, and 88.94% of impacts had a level of criticality compatible with the severity of the problem. Conclusion Predicting and classifying negative impacts are important stages in implementing electronic health records in hospitals. The method for identification and classification of impacts were, in most cases, considered effective.